Effect of treatment in weld surface on fatigue and fracture behavior of titanium alloys welded joints by vacuum electron beam welding. (July 2017) - Liu, Peng; Zhang, Ge-ming; Zhai, T.; Feng, Ke-yun
Abstract: The effect of treatment in weld surface on four-point bend fatigue properties and fracture characteristic of Ti–6.5Al–2Zr–1Mo–1V alloy by vacuum electron beam welding were tested and analyzed. When the excess weld metal and excess penetration are removed, the high fatigue strength of joints can be obtained. When the excess weld metal and excess penetration were not removed, the fatigue strength of joints is about 40% of yield strength of base metal. Two kinds of fatigue crack initiations can be observed under the upper surface of joint, which show the obvious local tearing fracture morphology and bulk inclusions or compounds morphology. Highlights: A novel fatigue analysis method on VEBW joint of titanium alloy was conducted. Effect of treatment in the weld surface on fatigue life was test and analyzed. The fracture behavior of VEBW joint of titanium alloys was analyzed.